Global Agri-Food Sector: Challenges and Opportunities in COVID-19 Pandemic - Hamid, Saima; Mir, Mohammad Yaseen (Frontiers in Sociology, 2021)
COVID-19 pandemic has been catastrophic for almost everything including the global economy. Among many sectors, the food and the agriculture sector was the worst hit following the immediate lockdown and market shutdowns. Though some stability was prevalent from supply side till date, however, the severe restrictions put in place to curb the spread of pandemic have endangered the supply of agricultural and food articles contemporaneously across borders and from field to fork. While the income decline due to price falland supplies chain disruptions due to pandemic have escalated the food shortages in several of developing and developed countries. Nevertheless the global demand for food items has remained more or less unchanged owing to their inelastic demand. Even within the global level, the scenario of food security and supply chain stability has been substantially deplorable for emerging and less developing countries due to their lack of insulation to the global shocks or pandemics. Notably, the technological backwardness, excessive know-how dependence and denied accessibility on several grounds lead to poverty and food hunger in these countries. At the policy level, a holistic approach specifically targeted towards the developing and less developed economies is highly warranted to ensure an appreciable progress towards the minimisation of sensitivity with regard to agriculture and food security. Apart from the measures to insulate them from global shocks, additional steps need to be taken to alleviate their technological backwardness and denied accessibility on certain socio-cultural norms.